2020
DOI: 10.3390/ijms21217841
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Function and Protein Turnover in the Diaphragm are Altered in LLC Tumor Model of Cancer Cachexia

Abstract: It is established that cancer cachexia causes limb muscle atrophy and is strongly associated with morbidity and mortality; less is known about how the development of cachexia impacts the diaphragm. The purpose of this study was to investigate cellular signaling mechanisms related to mitochondrial function, reactive oxygen species (ROS) production, and protein synthesis during the development of cancer cachexia. C57BL/J6 mice developed Lewis Lung Carcinoma for either 0 weeks (Control), 1 week, 2 weeks, 3 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…Findings from both preclinical and clinical studies confirm that the hallmarks of cancer cachexia are decreased myofiber cross-sectional area, disrupted muscle ultrastructure, and increased fibrosis [ 35 , 135 , 136 , 137 , 138 ]. Both depressed protein synthesis and accelerated proteolysis have been observed with muscle wasting due to cancer cachexia [ 139 , 140 , 141 , 142 ]. While the factors that contribute to cancer-induced muscle wasting are believed to be multifactorial, recent evidence has implicated mitochondrial dysfunction as a key contributor to cancer cachexia.…”
Section: Mitochondria and Cancer Cachexiamentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from both preclinical and clinical studies confirm that the hallmarks of cancer cachexia are decreased myofiber cross-sectional area, disrupted muscle ultrastructure, and increased fibrosis [ 35 , 135 , 136 , 137 , 138 ]. Both depressed protein synthesis and accelerated proteolysis have been observed with muscle wasting due to cancer cachexia [ 139 , 140 , 141 , 142 ]. While the factors that contribute to cancer-induced muscle wasting are believed to be multifactorial, recent evidence has implicated mitochondrial dysfunction as a key contributor to cancer cachexia.…”
Section: Mitochondria and Cancer Cachexiamentioning
confidence: 99%
“…As discussed previously, chronic elevation in mitochondrial ROS emissions can elicit muscle wasting. Evidence from preclinical models show that mitochondrial ROS emissions increase with cancer cachexia and are accompanied by increased markers of oxidative stress [ 35 , 138 , 139 , 150 , 151 ]. In contrast to these findings, some studies have reported decreased markers of muscle oxidative stress, and that exacerbated oxidative stress does not accentuate cancer cachexia [ 146 , 152 ].…”
Section: Mitochondria and Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a marked depletion in hepatic glycogen content has been reported in different preclinical models of cancer cachexia ( Narsale et al, 2015 ; Rosa-Caldwell et al, 2019 ), suggesting a conserved mechanism for alterations in hepatic metabolism across different cancer types. Cachectic liver also shows mitochondrial alterations in mouse models ( Rosa-Caldwell et al, 2020 ), which precede a fibrotic phenotype during the progression of cancer-cachexia also observed in patients ( Pinter et al, 2016 ; Judge et al, 2019 ). Similarly, it has been reported that liver mitochondria from tumor-bearing rats request a higher amount of nutrients to sustain the ATP production ( Dumas et al, 2011 ).…”
Section: Liver: Key Modulator Of Energy Expenditurementioning
confidence: 83%
“…Oral administration of coenzyme Q 10 (CoQ 10 ), a vitamin-like substance, improves mitochondrial biogenesis and function in skeletal muscle of Goto-Kakizaki rats [66]. Mitochondria biogenesis play a critical role in the metabolic and physiological adaptation of skeletal muscle [67]. Similarly, Liu et al reported that CoQ 10 administration ameliorates disuse-induced skeletal muscle atrophy via the activation of mitochondrial biogenesis and the amelioration of oxidative stress in SD rats.…”
Section: Vitaminsmentioning
confidence: 99%